ANALYZING THE QUALITY OF THEMATIC BASED QUR'AN LEARNING IN INTEGRATED ISLAMIC ELEMENTARY SCHOOLS IN PEKANBARU - Munawaroh, Faridatul; Sutrianingrum, Sutrianingrum (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Purpose: This study aims to analyze the quality of thematic-based Qur’an learning in Integrated Islamic Elementary Schools (SDIT) in Pekanbaru, focusing on the aspects of lesson planning, implementation, and evaluation by teachers. Method: The research employs a qualitative approach using a case study method. Data were collected through in-depth interviews, classroom observations, and document analysis at three SDITs in Pekanbaru and analyzed using the interactive model of Miles and Huberman. Result: The findings indicate that thematic-based Qur’an learning has a positive impact on students’ active engagement in the learning process as well as on their moral and spiritual development. Students become more enthusiastic, actively participate in thematic discussions, and demonstrate improved religious behavior such as honesty, responsibility, and social awareness. Theoretically, the findings enrich the discourse on pedagogical innovation based on Qur’anic values, while practically, they serve as a reference for Islamic schools in enhancing teacher competence, providing learning media, and designing balanced evaluations that address cognitive, affective, and psychomotor domains. Conclusion: Overall, thematic-based Qur’an learning proves to be an innovative model that not only improves academic quality but also fosters strong Qur’anic character among students.